Acute gastrointestinal illness in an African Indigenous population: the lived experience of Uganda's Batwa - Kaitlin Patterson; Sierra Clark; Lea Berrang-Ford; Shuaib Lwasa; Didacus Namanya; Fortunate Twebaze; IHACC Research Team; Sherilee Harper (James Cook University, 2020)
Introduction: Indigenous populations in low-income regions are often the most acutely affected by social gradients that impact health, including high burdens of infectious disease. Using a mixed methods approach, this study characterized the lived experience of acute gastrointestinal illness (AGI) in an Indigenous Batwa population in south-western Uganda. Methods: Quantitative data analyses were conducted on data from three cross-sectional census surveys of Batwa conducted in January 2013 (n=583), January 2014 (n=569) and April 2014 (n=540). Using a 14-day recall period, cases of AGI were defined as three or more loose stools or any vomiting in a 24-hour period. These analyses were supplemented by qualitative data from key informant interviews (n=11 interviews) and Batwa focus group discussions (n=61 participants). Results: From the surveys, episodes of diarrhea and episodes of vomiting lasted on average 3.6 (95%CI 2.3-4.3) and 3.0 (95%CI 2.1-3.9) days, and individuals experienced an average of 4.3 (95%CI 3.9-4.8) and 2.6 (95%CI 2.1-3.1) loose stools and vomiting episodes in 24 hours. Focus group participants and key informants indicated that episodes of AGI for Batwa were not limited to symptom-based consequences for the individual, but also had economic, social and nutritional impacts. Conclusion: Despite efforts to increase health literacy in disease transmission dynamics, risks and prevention measures, the perceived barriers and a lack of benefits still largely underscored adopting positive AGI prevention behaviors. This study moved beyond surveillance and provided information on the broader community-level burden of AGI and highlighted the current challenges and opportunities for improved uptake of AGI prevention measures for the Batwa.